2016
DOI: 10.3847/0004-637x/821/1/21
|View full text |Cite
|
Sign up to set email alerts
|

A Technique for Constraining the Driving Scale of Turbulence and a Modified Chandrasekhar–fermi Method

Abstract: The Chandrasekhar-Fermi (CF) method is a powerful technique for estimating the strength of the mean magnetic field projected on the plane of the sky. In this paper, we present a technique for improving the CF method in which we take into account the averaging effect arising from independent eddies along the line of sight (LOS). In the conventional CF method, the strength of fluctuating magnetic field divided bypr 4 , wherer is average density, is assumed to be comparable to the LOS velocity dispersion. However… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 27 publications
1
96
0
Order By: Relevance
“…Simulations show that this estimate can be corrected for a statistical ensemble of objects to yield realistic estimates of the field strength (Heitsch et al 2001;Ostriker et al 2001;Falceta-Gonçalves et al 2008). In addition, the effects of multiple eddies along the line of sight have been studied by Cho & Yoo (2016).…”
Section: Observing Magnetic Fieldsmentioning
confidence: 99%
“…Simulations show that this estimate can be corrected for a statistical ensemble of objects to yield realistic estimates of the field strength (Heitsch et al 2001;Ostriker et al 2001;Falceta-Gonçalves et al 2008). In addition, the effects of multiple eddies along the line of sight have been studied by Cho & Yoo (2016).…”
Section: Observing Magnetic Fieldsmentioning
confidence: 99%
“…We have shown that the conventional CF method tends to overestimate B 3D 0,sky if the driving scale is smaller than the system size and proposed a modified CF method that can correct the effect. The method we propose in Equation (23) with 0.7 < ξ ′ < 1.0 does not require new observations [5]. That is, the method is readily applicable for present observational data.…”
Section: Numerical Tests Of the Modified Cf Methodsmentioning
confidence: 93%
“…As we can see in the figure, the conventional CF method overestimates B 3D 0,sky as N eddy (∼ 1/k f ) increases. proportional to √ N eddy (see [5] for details). The centroid velocity is a kind of average velocity.…”
Section: Numerical Tests Of the Conventional Cf Methodsmentioning
confidence: 99%
See 2 more Smart Citations